The Relationship Between Earnings and Sexual Orientation: First Evidence from China - Zichen Deng; Weixiang Luo; Erik Plug; Jia Yu (Institute of Labor Economics (IZA), 2025)
We document, for the very first time, the relationship between earnings and sexual orientation in China. Using data from the 2020 Chinese Private Life Survey, we find that gay men earn significantly less than comparable heterosexual men, with the largest penalties for rural-hukou holders and among men reporting exclusive same-sex attraction. Lesbian women tend to earn more than heterosexual women, but the differences are small and mostly insignificant. The estimates for bisexual men and women are uniformly insignificant. We conclude that the gay penalties and lesbian premiums in China, albeit imprecisely estimated, mirror those observed in Western labor markets and are most consistent with explanations based on conventional gender norms and intra-household specialization.
Keywords: D10; J10; J15; J30; J70; O10; 330; sexual orientation; earnings; China